Detection of metabolites of benzo(a)pyrene in Sorbus sibirica Hedl. leaves and their use in the assessment of air pollution of Kemerovo City (Russian Federation) (Bangladesh Journal of Botany, 2013)
This article analyzes the ability of woody plants to metabolize benzapyrene and shows the assessment of the level of long-term air pollution in the city of Kemerovo by benzapirene from the industrial area with the help of modelling approach. Metabolites of benzo(a)pyrene - B(a)P-1,3-dione, 1-hydroxy-B(a)P and B(a)P- 7,8- dihydrodiol are identified in extracts of Sorbus sibirica Hedl. leaves. It is found that there is a close correlation between the sum of relative abundance of hydroxyl derivatives of benzapyrene (?OH-B(a)P) of S. sibirica leaves and air pollution by benzapirene (Q). DOI: http://dx.doi.org/10.3329/bjb.v42i1.15905 Bangladesh J. Bot. 42(1): 145-153, 2013 (June)